La création d’une communauté discursive sublimeLa propagande post-djihadiste de Boko Haram - Rinn, Michael (2023)
The article raises the question of the relationship between rhetoric as a tool for argumentation and negotiation used by a discursive community to safeguard its norms and rules of life, particularly in a crisis situation and the use of the sublime abject put in use by terrorist propaganda aimed at crushing the speakers through the spectacle of extreme violence. As if this violence were capable of transforming the very body of language, the latter being the necessary condition for making society. The analysis focuses on the post-jihadist propaganda discourse held by “Boko Haram”, a terrorist group which has also been involved in banditry in many countries of sub-Saharan Africa since 2015. After having noted the multiple and complex issues of the socio-historical context necessary to understand the acts of terrorist language, the article highlights the linguistic functioning of this type of discourse, the purpose of which is not only to put civilian populations under the yoke of fear, but to produce a sublime discursive community entirely given over to single thought.
Keywords: discourse analysis; rhetoric; argumentation; sublime; propaganda; terrorism; violence